The Bambuí health and ageing study (BHAS): methodological approach and preliminary results of a population-based cohort study of the elderly in Brazil Estudo de Bambuí sobre saúde e envelhecimento: metodologia e resultados preliminares de coorte de estudo de idosos no Brasil - Maria Fernanda F Lima e Costa; Elizabeth Uchoa; Henrique L Guerra; Josélia OA Firmo; Pedro G Vidigal; Sandhi M Barreto (Universidade de São Paulo, 2000)
OBJECTIVE: A cohort study has been designed to identify predictors of adverse health events in the elderly. The methodology of the study and preliminary descriptive results are presented. METHODS: The study population comprises all residents of Bambuí (Minas Gerais, Brazil), aged 60 or more years (n=1.742). From these, 92.2% were interviewed and 85.9% underwent clinical examination, consisting of haematological and biochemical tests, serology for Trypanosoma cruzi, anthropometric and blood pressure measures and electrocardiogram. Aliquots of serum, plasma and DNA were stored for future investigations. The baseline interview included sociodemographic characteristics, self-referred health condition and history of selected diseases, medication use, health service use, source of medical care, physical activities, smoking, drinking and eating habits, reproductive history, physical functioning, life events, social support and mental health. Individuals are being followed up annually. RESULTS: The following characteristics predominated among participants: women (60,0%), married (48.9%) or widowed (35.4%), people living in households with up to 2 residents (73.8%), heads of family (76.7%), people with monthly income between 1.00 and 2.99 Brazilian minimum wages (62.0%) and people with up to 4 years of schooling (89.1%). The median age was 68 years. Among the cohort members, only 1.7% were lost in the first follow-up. CONCLUSIONS: In general, the characteristics of the study population were very similar to those from other epidemiological studies of the elderly based on large Brazilian cities. The small number of losses to follow-up indicates that the choice of Bambuí was adequate, assuring the feasibility of a long term cohort study. OBJETIVO: Um estudo de coorte está sendo desenvolvido para identificar fatores preditores de eventos adversos à saúde em idosos. São apresentados a metodologia do estudo e os resultados descritivos preliminares. MÉTODOS: A população estudada é constituída por todos os residentes na cidade de Bambuí, Minas Gerais, com 60 ou mais anos de idade (n=1.742). Destes, 92,2% foram entrevistados e 85,9% foram submetidos a exames hematológicos e bioquímicos, sorologia para Trypanosoma cruzi , medidas antropométricas e de pressão arterial e eletrocardiograma. Alíquotas de soro, plasma e DNA foram estocadas para futuras investigações. A entrevista da linha de base do estudo incluiu: características sociodemográficas, percepção da saúde e morbidade auto-referida, uso de medicamentos, acesso a serviços de saúde e a planos de saúde, atividades físicas, uso de fumo e de álcool, hábitos alimentares, história reprodutiva, função física, eventos da vida, recursos sociais e saúde mental. Os participantes estão sendo acompanhados anualmente. RESULTADOS: As seguintes características predominaram entre os participantes: mulheres (60%), casados (48,9%) ou viúvos (35,4%), residentes em domicílios com até 2 pessoas (73,8%), chefes de família (76,7%), pessoas com renda mensal entre 1 e 2,99 salários-mínimos (62%) e pessoas com 4 ou menos anos de escolaridade (89,1%). A mediana da idade foi igual a 68 anos. Somente 1,7% dos membros da coorte foram perdidos no primeiro acompanhamento. CONCLUSÕES: Em geral, as características da população estudada foram muito semelhantes às de participantes de outros estudos epidemiológicos sobre envelhecimento, desenvolvidos em grandes cidades brasileiras. A pequena perda para acompanhamento mostra que a escolha de Bambuí foi adequada, garantindo a viabilidade de um estudo prospectivo de longa duração.